Pemberian Makanan Pendamping ASI Dini Berhubungan dengan Kejadian Diare pada Bayi umur 0 – 12 bulan di Kecamatan Dampal Utara, Tolitoli, Sulawesi Tengah - Oktaviana Maharani (Jurnal Ners dan Kebidanan Indonesia, 2016)
Diarrhea is the number one cause of infant mortality worldwide. The United Nations Children’s Emergency Fund (UNICEF) estimates that every 30 seconds there is a child who died of diarrhea in Indonesia. The incidence of diarrhea in young children one of them caused by hygiene including the knowledge and attitudes of mothers in feeding, where the baby has been fed besides breast milk (breast milk) before the age of 6 months. According to the World Health Organization, infants who received complementary foods before six months of age will have a 17 times greater risk of experiencing diarrhea. The aim of research to determine feeding complementary relationship with the incidence of diarrhea in infants aged 0-12 months in the District of North Dampal, Tolitoli, Central Sulawesi. The population in this experiment is all mothers with babies aged 0-12 months who are in the district of North Dampal, Tolitoli, Central Sulawesi, which amounted to 36 mothers. Samples were taken using a total sampling. Data were analyzed using chi-square test. The results showed there are significant relationship between the giving weaning food with the incidence of diarrhea in infants 0-12 months in North Dampal, Tolitoli, Central Sulawesi.